Huwelik of nie – wat van Hooglied? - Viviers, Hennie (Verbum et ecclesia, 2006)
The traditional heterosexual, monogamous marriage can be questioned, not only on the grounds of modern deviating practices in regard to permanent love relationships but on discrepancies within the Bible itself. It is a myth that the "Bible says…" and then voicing only one viewpoint, when there are more than what fundamentalists have Bible readers to believe. The Song of Songs represents such an alternative voice, subverting the mainstream mores of its time. It not only subverts what was then deemed "proper", patriarchy, class and religion but markedly also the typical Mediterranean marriage. The two lovers dream of a traditional marriage some time in the future but at the moment they focus predominantly on the intimate enjoyment of each other. "Sex before marriage", however, is never promiscuous but adheres to a deapseated ethic of fidelity. The Song interestingly opens up morally defendable permanent relationships other than the traditional marriage. Utilizing Body Criticism the Song is appreciated in its own right in this article.